2020
DOI: 10.1029/2019ea000911
|View full text |Cite
|
Sign up to set email alerts
|

First Observation of Ionospheric Convection From the Jiamusi HF Radar During a Strong Geomagnetic Storm

Abstract: The Super Dual Auroral Radar Network (SuperDARN) is an international low-power high-frequency (HF) radar network, which provides continuous observations of the motion of plasma in the ionosphere. Over the past 15 years, the network has expanded dramatically in the middle latitudes of the Northern Hemisphere to improve the observation capabilities of the network during periods of strong geomagnetic disturbance. However, a large coverage gap still exists in the middle latitudes. A newly deployed middle-latitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The other three storms, characterized by the minimum Dst indices around −50 nT and the Kp indices over 4, appear with the commencement of the recovery phase on September 11, September 22, and October 8, respectively. The strongest storm on August 26 has been widely reported (e.g., Chen et al., 2019; Hübert et al., 2020; Zhang et al., 2020), while the other three storms are rarely discussed in previous studies. Note that those four storms are observed with a characteristic of periodicity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The other three storms, characterized by the minimum Dst indices around −50 nT and the Kp indices over 4, appear with the commencement of the recovery phase on September 11, September 22, and October 8, respectively. The strongest storm on August 26 has been widely reported (e.g., Chen et al., 2019; Hübert et al., 2020; Zhang et al., 2020), while the other three storms are rarely discussed in previous studies. Note that those four storms are observed with a characteristic of periodicity.…”
Section: Discussionmentioning
confidence: 97%
“…In the autumn of 2018, a strong geomagnetic storm occurred on August 26 (e.g., Chen et al., 2019; Hübert et al., 2020; Zhang et al., 2020). This storm caused significant ionospheric perturbations in both the European sector (Blagoveshchensky & Sergeeva, 2020) and the China sector (Yang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The median LOS velocity is used in the statistical analysis of mid-latitude ionospheric convection velocity distribution. Zhang et al (2020) reported the first observations of the ionospheric convection from the Jiamusi radar during a strong geomagnetic storm. Their study showed that the Jiamusi radar and Hokkaido East radar observed flow of the same irregularities during the storm.…”
Section: Data Selection and Processingmentioning
confidence: 99%
“…Zhang et al. (2020) have presented their first observation result during a strong geomagnetic storm. The JME radar site's geographic coordinates are 46.8°N, 130.5°E, and the boresight is 44° north to east in geographic coordinates.…”
Section: The Amplitude and Phase Imbalance Analysis In Agiledarnmentioning
confidence: 99%
“…This study is to present the calibration method of the Agile Dual Auroral Radar Network (AgileDARN). The AgileDARN radar has been developed as a new generation of all‐digital Super Dual Auroral Radar Network (SuperDARN) radar by the National Space Science Center, Chinese Academy of Sciences (NSSC, CAS) (Deng et al., 2020; Jiang et al., 2018; Yan et al., 2020; Zhang et al., 2020). The SuperDARN is known as an international collaboration of low‐power, high‐frequency (HF) radars making measurements of detecting backscatter from plasma density irregularities in the high‐ and mid‐latitude ionosphere for scientific purposes.…”
Section: Introductionmentioning
confidence: 99%